Pore Structure and Gas Diffusion Features of Ionic Liquid-Derived Carbon Membranes - Ourania Tzialla; Anastasios Labropoulos; Georgios Pilatos; Georgios Romanos; Konstantinos G. Beltsios (C, 2022)
In the present study, the concept of Ionic Liquid (IL)-mediated formation of carbon was applied to derive composite membranes bearing a nanoporous carbon phase within their separation layer. Thermolytic carbonization of the supported ionic liquid membranes, prepared by infiltration of the IL 1-methyl-3-butylimidazolium tricyanomethanide into the porous network of Vycor® porous glass tubes, was applied to derive the precursor Carbon/Vycor® composites. All precursors underwent a second cycle of IL infiltration/pyrolysis with the target to finetune the pore structural characteristics of the carbonaceous matter nesting inside the separation layer. The pore structural assets and evolution of the gas permeation properties and separation efficiency of the as-derived composite membranes were investigated with reference to the duration of the second infiltration step. The transport mechanisms of the permeating gases were elucidated and correlated to the structural characteristics of the supported carbon phase and the analysis of LN2 adsorption isotherms. Regarding the gas separation efficiency of the fabricated Carbon/Vycor® composite membranes, He/CO2 ideal selectivity values as high as 4.31 at 1 bar and 25 °C and 4.64 at 0.3 bar and 90 °C were achieved. In addition, the CO2/N2 ideal selectivity becomes slightly improved for longer second-impregnation times.